2018
DOI: 10.1177/0738894218759008
|View full text |Cite
|
Sign up to set email alerts
|

Fatal attraction: explaining variation in the attractiveness of Islamic State propaganda

Abstract: Why do different Islamic State propaganda products receive different numbers of views? This article relies on a dataset of 1700 Islamic State photo essays to examine this question. It finds that violence in Islamic State photo essays, especially retributional violence, or violence directed at the group’s enemies and wayward adherents, leads to increased viewership. Releases that highlight the group’s military operations, governance activities and geographic expansion also draw more attention, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Other studies show that when rebels conduct attacks with high levels of victims, they tend to lose online support when this information circulates in social media platforms (Barceló and Labzina 2020). In contrast, when rebels publish that they limit their violence against their opponents, they tend to receive more support (Milton 2020).…”
Section: The Internet and Popular Supportmentioning
confidence: 99%
“…Other studies show that when rebels conduct attacks with high levels of victims, they tend to lose online support when this information circulates in social media platforms (Barceló and Labzina 2020). In contrast, when rebels publish that they limit their violence against their opponents, they tend to receive more support (Milton 2020).…”
Section: The Internet and Popular Supportmentioning
confidence: 99%
“…For example, the promotion of images of civilians being tortured or assassinated is not only a form of brutal violence, but an element that emphasizes the emotional justification of such acts, and the type of activities that terrorists usually engage with [50]. Even more, in the case of ISIS, it can be observed that the group usually uses violence in order to attract attention and evoke emotions [51].…”
Section: Terrorist Propaganda and The Profile Of The Socio-emotional Intelligent Terroristmentioning
confidence: 99%
“…Indeed, the Islamic State’s media enterprise itself utilized a wide variety of tactics in an effort to wage war in the information domain, many of which have been the focus of scholarly research (e.g. Colas, 2017; Farwell, 2014; Ingram, 2015; Jadoon and Mahmood, 2017; Lakomy, 2020; Mahood and Rane, 2017; Milton, 2018a; Pennington and Krona, 2019; Winkler et al, 2019; Winter, 2018). However, despite this important research, few scholars have examined the group’s attempts to further its goals through the deliberate use of deception in propaganda, or that of militant organizations more broadly.…”
Section: Introductionmentioning
confidence: 99%